Core Outcome Measures for Clinical Research in Acute Respiratory Failure Survivors. An International Modified Delphi Consensus Study - Needham, Dale M. (Am J Respir Crit Care Med, 2017)
Rationale: Research evaluating acute respiratory failure (ARF) survivors’ outcomes after hospital discharge has substantial heterogeneity in terms of the measurement instruments used, creating barriers to synthesizing study data. Objectives: To identify a minimum set of core outcome measures that are essential to include in all clinical research studies evaluating ARF survivors after discharge. Methods: We conducted a three-round modified Delphi consensus process with 77 participants (47% female, 55% outside the United States), including clinical researchers from more than 16 countries across six continents, patients/caregivers, clinicians, and research funders. Participants reviewed standardized information on measure instruments for seven consensus-derived outcomes plus one recommended outcome. Measurements and Main Results: Response rates were 91 to 97% across the three rounds. Among 75 measurement instruments evaluated, the following met a priori consensus criteria: EQ-5D and 36-item Short Form Health Survey version 2 (optional) for the “satisfaction with life and personal enjoyment” and “pain” outcomes, and both the Hospital Anxiety and Depression Scale and the Impact of Events Scale–Revised for the “mental health” outcome. No measures reached consensus for the following outcomes: cognition, muscle and/or nerve function, physical function, and pulmonary function. All measures considered for pulmonary function met consensus criteria for exclusion. The following measures did not reach the threshold for consensus but achieved the highest scores for their respective outcomes: the Montreal Cognitive Assessment (cognition), manual muscle testing and handgrip dynamometry (muscle and/or nerve function), and 6-minute-walk test (physical function). Conclusions: This Core Outcome Measurement Set is recommended for use in all clinical research evaluating ARF survivors after hospital discharge. In the future, researchers should evaluate measures for outcomes not reaching consensus.